A política fundiária do governo Olívio Dutra no Rio Grande do Sul - Brasil (1999-2002): diretrizes, dinâmica política e resultados atingidos - Da Ros, César Augusto (2007)
This paper has as objective to analyze the foundry work politics made by the Olívio Dutra's government in the state of Rio Grande do Sul-Brazil, being taken into account their guidelines, the dynamics of the political struggle promoted between the social leaders from the rural area and the achieved global results. This government's freshness is related to the fact of it was being sustained and supported by a coalition of left wing parties and by a group of social movements and also by syndical entities of the field, which was decisive in the presentation of an antagonistic program to the neoliberal politics on energy in a national extent. Hence this government became committed in adopting an own foundry work politics, being opposed to the program of market land reform extolled by Cardoso's government, in national wide. Therefore, the results presented along the article demonstrate that in spite of the assumed commitments and, in face of legal, institutional and economical limitations and also its existent politics, the space of the state governments' performance can only be thought about its complemental character on the federal government's actions.
Este artigo tem por objetivo analisar a política fundiária executada pelo governo Olívio Dutra, no estado do Rio Grande do Sul - Brasil, levando-se em consideração as suas diretrizes, a dinâmica da luta política travada entre os atores sociais do meio rural e os resultados globais atingidos. O ineditismo deste governo está relacionado ao fato deste ter sido sustentado e apoiado por uma coalizão de partidos de esquerda e por um conjunto de movimentos sociais e entidades sindicais do campo, o que foi determinante na apresentação de um programa antagônico às políticas neoliberais em vigor em âmbito nacional. Por essa razão este governo comprometeu-se em adotar uma política fundiária própria, opondo-se ao programa de reforma agrária de mercado preconizado pelo governo Cardoso, em nível nacional. Os resultados apresentados ao longo do artigo demonstram que a despeito dos compromissos assumidos e, em face das limitações legais, institucionais, econômicas e políticas existentes, o espaço de atuação dos governos estaduais somente pode ser pensado em caráter complementar as ações do governo federal.
Keywords: Foundry work politics; Political struggle; Rural social movements; Política fundiária^lpt; Luta política; Movimentos sociais do campo; Política; Economía; Historia rural